2018
DOI: 10.3382/ps/pex436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-protein diets on acute phase proteins and heat shock protein 70 responses, and growth performance in broiler chickens under heat stress condition

Abstract: A study with a 4 × 2 factorial arrangement was conducted to investigate the effects of 4 dietary protein levels and 2 environmental conditions on acute phase proteins (APP), brain heat shock protein (HSP) 70 density, and growth performance of broiler chickens. Day-old broiler chicks (Cobb 500) were fed isocaloric diets but with various levels of crude protein (CP), namely, (1) 21.0 and 19.0% CP in starter and finisher diets, respectively (control), (2) 19.5 and 17.5% CP in starter and finisher diets, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…However, feeding LPRE, LPREP, RPLE or RPLEP diet had no detrimental effects on the bird's performance under both normal and heat stress conditions. Zaman et al (2008) reported a beneficial effect of feeding low-CP at recommended ME diet under HS, outcomes which disagree with many other works when low-CP (Alleman and Leclercq 1997;Zulkifli et al 2018) or low-CP and low-ME diets (Attia and Hassan 2017) were fed to broilers under the same conditions. These inconsistencies could be associated with differences in the levels of dietary CP, supplemented AA and/or the severity of heat challenge involved.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…However, feeding LPRE, LPREP, RPLE or RPLEP diet had no detrimental effects on the bird's performance under both normal and heat stress conditions. Zaman et al (2008) reported a beneficial effect of feeding low-CP at recommended ME diet under HS, outcomes which disagree with many other works when low-CP (Alleman and Leclercq 1997;Zulkifli et al 2018) or low-CP and low-ME diets (Attia and Hassan 2017) were fed to broilers under the same conditions. These inconsistencies could be associated with differences in the levels of dietary CP, supplemented AA and/or the severity of heat challenge involved.…”
Section: Discussionmentioning
confidence: 59%
“…The current study demonstrated that HS elevated CORT and APPs (CPN, OVT and AGP) in broilers. It is well documented that heat exposure can elevate CORT (Mahmoud et al 2004;Soleimani et al 2011;Najafi et al 2015), APPs (Najafi et al 2015;Zulkifli et al 2018) and HSP 70 expression (Mahmoud et al 2004;Najafi et al 2015;Zulkifli et al 2018) in broilers. In the present study, reducing dietary CP and ME did not affect CORT level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations